LENGTH-WEIGHT RELATIONSHIP AND CONDITION FACTOR OF FISH SPECIES OF OGUTA LAKE, IMO STATE, NIGERIA - AGORUA, U. N; SIKOKI, F. D.; VINCENT-AKPU , I. F. (Nigerian Journal of Fisheries, 2021)
Length-weight relationship and condition factor of Oguta Lake, Imo State, Nigeria was studied for 18 months (May 2016- October 2017) with 48 species sampled. The length-weight relationship (LWR) was calculated with the formulaW=aLb and the condition factor using Fulton Condition Factor (K) formula. The length-weight relationship shows that ’b’ (growth exponent) ranged between 0.2875 and 5.1319 with Arnoldichthys spilopterus having the lowest value whereas the highest value was recorded for Petrocephalus bane bane. Most of the species exhibiteda negative allometric growth pattern. Citharinus citharus citharus, Gymnarchus niloticus, Heterotis niloticus, Labeo senegalensis, Parachelon grandisquamis, Schilbe mystus, and Petrocephalus bane bane exhibited positive allometric growth pattern while Alestes dentex and Synodontis courteti exhibited isometry growth pattern. The mean values of the condition factor (K) ranged 0.14±0.02-7.07±4.90 with the lowest mean value recorded for Polypterus senegalus senegalus and the highest recorded for Tetraodon lineatus. Thelowest condition factor 0.19 was recorded for Gymnarchus niloticus. This shows that most of the species are not in a good state which may be caused by inadequate feeding, environmental or physiological condition. Therefore, this calls for enforcement of regulations, adequate fishery management, and close monitoring of length-weight relationship and condition factor of the species for effective stock management of the lake